ABA deficiency and its impact on ion and metabolite profiles in tomato roots under single and combined stress conditions - Miriam Pardo-Hernández; Pascual García-Pérez; Luigi Lucini; Rosa M Rivero (Plant Stress, 2024)
Abscisic acid (ABA) plays a crucial role in the stress response of plants. Although the impact of ABA on individual stresses has been extensively studied, there is less research on its role in plants grown under stress combination, such as salinity and high temperature. This study analyzes the response at the ionomic and metabolomic levels of tomato roots to ABA deficiency under single salinity or heat stress, as well as under the combination of both stresses, using ABA-deficient (flacca, flc) tomato plants. ABA was found to be crucial in ionic regulation, particularly for Na, K, Ca, and other ions such as Cu, Mn, Zn, Mo, and Fe. However, its influence depended on the type of stress applied, indicating the complexity of plant responses to these adverse environmental factors. In our study, phenylpropanoids, terpenoids, and nitrogenous compounds were the metabolites most affected by endogenous ABA concentration and environmental treatment. On the other hand, the application of exogenous ABA to flc mutants did not fully restore root dry weight, although it did cause significant changes at the ionomic and metabolomic levels. Salinity and heat applied in combination aggravated the vulnerability of flc mutants compared to single stresses, making the application of exogenous ABA more effective under single stresses than under the combined stresses. Finally, a correlation analysis between the ionome and metabolome revealed that the accumulation or deficiency of some ions (i.e., Na, Zn, and Fe) was correlated with the abundance of important metabolites related to amino acid biosynthesis and terpenoid metabolism, among others.